Three new species of the genus Pseudachorutella Stach, 1949 (Collembola, Neanuridae) from Russia - Babenko, Anatoly; Kuznetsova, Natalia (Zootaxa, 2024)
Three new species of the genus Pseudachorutella, namely P. circassiana sp. nov., P. plurichaetosa sp. nov. and P. stebaevae sp. nov., are described from different regions of the Russian Federation. The former two new species represent the Caucasian fauna, whereas the latter is from southern Siberia. Both P. plurichaetosa sp. nov. and P. stebaevae sp. nov. seems to be especially similar to P. bescidica, from the Polish Carpathians, in showing the rich dorsal chaetotaxy characteristic of all these species. In contrast, P. circassiana sp. nov. shows a chaetotaxy comparable to that of the widespread P. asigillata and the Mediterranean P. ellisi. The latter three species can be distinguished by the length and shape of the buccal cone.